2017
DOI: 10.1016/j.nimb.2017.04.034
|View full text |Cite
|
Sign up to set email alerts
|

Atomistic simulation of ion irradiation of semiconductor heterostructures

Abstract: Recently the possibility to use ion beam mixing combined with suitable annealing has been suggested as a possible means to synthesize individual silicon quantum dots in a silica layer, with the possibility to function as single-electron transistors. For this to work, it is necessary to have a careful control of the ion beam mixing in Si/SiO 2 /Si heterostructures, as well as understand the nature of not only the composition, but also the chemical modication of the SiO 2 layer by the mixing with Si. We describe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…However, in recent experiments [15,[25][26][27], it was demonstrated that the 30 eV Ar ion irradiation caused the ripple formation on the surface of amorphous Si as well. In the current work, we gain new insights on the process of ripple formation due to a unique combination of a recently developed speedup scheme for MD simulation [28] to simulate tens of thousands of ion impacts on the same surface, with consideration of the new experimental condition of very low ion energy-induced ripples. The application of this new MD scheme enables us to observe directly the ripple formation and propagation by atomic self-organization at low energy irradiation, and to show that under negligible sputtering, the accumulation of displacement is the driving force of the ripple propagation similar to that observed experimentally.…”
Section: Introductionmentioning
confidence: 99%
“…However, in recent experiments [15,[25][26][27], it was demonstrated that the 30 eV Ar ion irradiation caused the ripple formation on the surface of amorphous Si as well. In the current work, we gain new insights on the process of ripple formation due to a unique combination of a recently developed speedup scheme for MD simulation [28] to simulate tens of thousands of ion impacts on the same surface, with consideration of the new experimental condition of very low ion energy-induced ripples. The application of this new MD scheme enables us to observe directly the ripple formation and propagation by atomic self-organization at low energy irradiation, and to show that under negligible sputtering, the accumulation of displacement is the driving force of the ripple propagation similar to that observed experimentally.…”
Section: Introductionmentioning
confidence: 99%
“…[196][197][198] Generally, the ion beam irradiation method is combined with post-treatment such as exposure to precursor gases or thermal annealing to optimize the defect-related properties of the heterostructures. [180,199] Suitable thermal annealing could control the ion-generated defects, and exposure to precursor gases would dope the defect structure with desired molecules, which are important for the electronic structure engineering in vdW heterostructures.…”
Section: Particle Beam Irradiation Methodsmentioning
confidence: 99%
“…To simulate a large number of cascades within a reasonable computational time, we applied the same speedup procedure as described in Ref. 32: ten ion impacts simulated only for 1.0 ps each followed by a 5.0 ps long relaxation with the Berendsen thermostat applied to all atoms. During the active phase of cascade development, the thermostat was applied only to the atoms in the pedestal.…”
Section: High-fluence Ion Irradiation Of the Nanopillarsmentioning
confidence: 99%